APPLICATION OF WAVELET-TRANSFORM AND PRONY METHOD FOR THE BIOGENIC SIGNALS IDENTIFICATION - Anna V. KOLOMEYTSEVA; Galina V. MISHUGOVA; Alexandra P. MUL; Galina Y. RYABYKH (Advanced Engineering Research)
Non-stationary signals of biogenic character (cardiogram, eleсtroencephalogram, etc.) are considered. Analysis of signals with the use of wavelet-transform and Prony method - which unlike classical Fourier method make an improved spectral evaluation - is applied.